6 - La lutte anti-corruption : l’expérience des pays d’Asie du Sud-Est: DOI: 10.4314/ad.v31i1.22253 - Dialla, Basga Emile (Africa Development, 2006)
Although corruption has always existed throughout the history of mankind, it has become lately the major concern of the international community because of its underground characteristics and its corrosive impact on economic growth. Ignored for long time by sociological research, corruption refers to any form of embezzlement and appears as a consequence of the market economy. Actually, corruption thrives in countries with weak institutions due to the pressure on other sectors from the market economy. In sum, corruption against which the fight will be long and hard appears within an institutional vacuum. The strategy to fight corruption should involve all social segments and the international community, and combine strong political will, citizen information and punishment. To that respect, African countries may learn somehow from the South East Asian countries’ experience.